Spirito delle leggi (dai Quesiti sull’Enciclopedia, 1771) - Voltaire, François-Marie Arouet (Montesquieu.it, 2011)
Italian translation, by Domenico Felice, of Voltaire’s article Esprit des lois (Questions sur l’Encyclopédie).